El cruel abrazo del dolor: la endometriosis y sus representaciones - Galli, Ida; Luongo, Assunta; Ramirez Cortázar, Felipe; Fasanelli, Roberto (Pontificia Universidad Católica del Perú, 2024)
Endometriosis is a chronic disease of the female genital tract, the etiology of which is still unclear. The purpose of this paper is to analyze, from a biopsychosocial perspective, the structure of social representations of endometriosis of women with this disease and healthy women. To this end, an exploratory survey was conducted by administering an online questionnaire. The results made it possible to identify those particular type of social representations, the controversies, articulated differently and often contradictory in their peripheral elements. These results provide a useful basis for the construction of intervention strategies to avoid the “epistemological purgatory” in which many women are forced to live due to the discrepancy between the subjective experience of endometriosis and its expert knowledge.

La endometriosis es una enfermedad crónica del aparato genital femenino cuya etiología aún no está clara. El objetivo de este trabajo es analizar, desde una perspectiva biopsicosocial, la estructura de las representaciones sociales de la endometriosis entre mujeres con esta enfermedad y mujeres sanas. Para ello, se realizó una encuesta exploratoria mediante un cuestionario online. Los resultados permitieron identificar ese tipo particular de representaciones sociales, las polémicas, articuladas de manera diferente y a menudo contradictoria en sus elementos periféricos. Estos resultados constituyen una base útil para la construcción de estrategias de intervención destinadas a evitar el “purgatorio epistemológico” en el que muchas mujeres se ven obligadas a vivir debido a la discrepancia entre la experiencia subjetiva de la endometriosis y el conocimiento experto de la misma.

L’endométriose est une maladie chronique de l’appareil génital féminin dont l’étiologie n’est pas encore élucidée. L’objectif de ce travail est d’analyser, dans une perspective biopsychosociale, la structure des représentations sociales de l’endométriose chez les femmes atteintes de cette maladie et chez les femmes saines. Pour faire ça, une enquête exploratoire a été menée au moyen d’un questionnaire en ligne. Les résultats ont permis d’identifier un type particulier de représentations sociales, les représentations polémiques, articulées différemment et souvent contradictoires dans leurs éléments périphériques. Ces résultats fournissent une base utile pour construire des stratégies d’intervention afin d’éviter le «purgatoire épistémologique» dans lequel de nombreuses femmes sont contraintes de vivre en raison du décalage entre leur expérience subjective de l’endométriose et la connaissance qu’en ont les experts.

A endometriose é uma doença crónica do aparelho genital feminino, cuja etiologia ainda não está esclarecida. O objetivo deste trabalho é analisar, numa perspectiva biopsicossocial, a estrutura das representações sociais da endometriose entre mulheres com esta doença e mulheres saudáveis. Para o efeito, foi realizado um inquérito exploratório através de um questionário online. Os resultados permitiram identificar um tipo particular de representações sociais, as polémicas, articuladas de forma diferente e muitas vezes contraditória nos seus elementos periféricos. Estes resultados constituem uma base útil para a construção de estratégias de intervenção para evitar o “purgatório epistemológico” em que muitas mulheres são obrigadas a viver devido à discrepância entre a sua experiência subjetiva da endometriose e o seu conhecimento especializado da mesma.
The cruel embrace of pain: endometriosis and its representations
L’étreinte cruelle de la douleur: l’endométriose et ses représentations
Keywords: Endometriosis; Social representations; Mixed methods; Physician-patient communication; Endometriosis; Representaciones sociales; Métodos mixtos; Comunicación médico-paciente; Endométriose; Représentations sociales; Méthodes mixtes; Communication médecin-patient; Endometriose; Representações sociais; Métodos mistos; Comunicação médico-doente; https://purl.org/pe-repo/ocde/ford#5.01.00